Estrategias de afrontamiento en estudiantes universitarios de Latinoamérica y Europa con estrés académico - Quezada Matute, María José (2024)
The importance of mental health has gained prominence as its effects on the biopsychosocial well-being of individuals have become more evident. Within this framework, academic stress emerges as one of the main sources of mental deterioration, highlighting the need to investigate how individuals cope with this challenge. The following study is presented, focused on the coping strategies adopted by university students to manage academic stress. The general objective of this study is to describe the scientific evidence of overcoming strategies in academic stress among university students in Latin America and Europe. A descriptive literature review was conducted using the PRISMA diagram, with a qualitative approach and non-experimental design. The databases used were: Scielo, Dialnet, and Redalyc. Thus, a total of 21 articles were used for this research in the Spanish language, with a maximum publication date of 20 years. The results obtained from this study demonstrate that social support and positive reevaluation are common strategies. Additionally, the main situations that trigger academic stress are educational overload and limited time for task completion. Furthermore, the study presents a guide manual on time management tools as a preventive intervention to reduce dysfunctional stress and increase appropriate overcoming strategies